Pancreatic Cancer: Molecular, Biochemical, Chemopreventive, and Therapeutic Aspects - Juan Iovanna; José Luis Neira (The Scientific World Journal)
Pancreatic cancer (PC) is the fourth leading cause of cancer death, with a median survival of 6 months and a dismal 5-year survival rate of 35%, a figure which has remained relatively unchanged over the past 25 years. PC is one of the most difficult diseases to treat due to late initial diagnosis and to resistance to the usual treatments. The presence of occult or clinical metastases at the time of diagnosis, together with the lack of effective chemotherapies, contributes to the high mortality in patients with PC. Its lethal nature stems from its propensity to disseminate rapidly to the lymphatic system and distant organs. Yet, understanding and stopping metastasis may prove to be one of the great potential strategies of treating PC. There is a dire need for the design of new and targeted therapeutic strategies that can overcome the drug resistance and improve the clinical outcome for patients diagnosed with the illness. The knowledge of the molecular aspects of PC is very important, and it is likely to be helpful in the design of newer drugs and the molecular selection of existing agents for targeted therapy. The inhibition of signal pathways can be carried out not only by small molecules, able to bind to selected regions of the target protein, but also by using large molecules as antibodies. The pathway to successful new therapies has been inhibited because of the rapidity with which agents tend to move into randomized, controlled trials without the extensive early testing necessary to optimize treatment regimens. However, lessons have been learned and our collective research effort has generated a substantial platform of knowledge from which further work will spring. The bioavailability of compounds such as antisense oligonucleotides and siRNAs in humans remains a big hurdle, which will require further improvement of gene-delivery strategies. Finally, the long-term goal of the therapy individualization for patients is possible if factors that predict treatment response, such as biological markers, could be determined accurately. These approaches are likely to comprise a mixture of targeted agents in combination with conventional chemotherapy and radiotherapy. For a clinically significant effect to be achieved, treatment strategies should either be in the form of (1) a horizontal approach, in which several oncogenic pathways (as those described in this series of reviews) are inhibited; or (2) a vertical approach, whereby multiple levels of a major pathway are targeted. Combination therapies, together with improved diagnostic tools and predictive markers, are ultimately desired in order to improve the bleak outlook for patients diagnosed with PC.